Globalisation and the State: Theoretical Paradigms - Nordhaug, Kristen
The article identifies fives theoretical positions in the debate on the effect of globalisation on national policies and institucions with a focus on issues of financial liberalisation in emergins economies. These positions are distinguished in terms of their asumptions about the main systemic level of causal influences on national policies and their assumption about convergence/divergence of national policies and institutions. Five levels of systemic impact are identified: transnational economic influence national political influence internacional, trnasnational and global political influences. The article concludes with a discussion of prospects for "unpacking" and combining the theories with examples relating to East Asian financial policies